Genetic diversity and phylogenetic relationship of Indonesian Local goats using microsatellite DNA markers - M Syamsul Arifin Zein; S Sulandari; Muladno .; Subandriyo .; Riwantoro . (Indonesian Center for Animal Research and Development (ICARD), 2012)
Genetic diversity is important information in the process of conservation and sustainable utilization of animal genetic resources. Thirteen microsatellite markers were used to estimate the degree of genetic diversity on five Indonesian local goats. Results showed the highest average allele diversity present in the locus MAF70 (5.6 ± 2.9), and the lowest was in the locus MAF035 (1.6 ± 0.6), the average number of alleles per locus was 6 ± 2.3. The lowest average alleles diversity present was in the Gembrong goat (2.2 ± 1.1) and the highest was in the Jawarandu goat (4.9 ± 2.2). There is a unique alleles at loci MCM527 and present in all Indonesian local goat with the highest allele frequency on Peranakan Etawa (37.2%) and lowest in Gembrong goat (7.9%). H0 ranged from 0.372 ± 0.173 (Gembrong) to 0.540 ± 0.204 (Peranakan Etawa), and HE ranging from 0.249 ± 0.196 (Gembrong) to 0.540 ± 0.212 (Peranakan Etawa).The genetic differentiation for inbreeding among population (FIS), within population (FIT), and average genetic differention (FST) were 0,0208 (2,08%), 0,1532 (15,32%), and 0,1352 (13,52%), respectively. Locus ILSTS029, BMS1494, MAF035 and INRA0132 had a low PIC value (PIC < 0.25), locus SRCRSP3, OARFCB20, ILSTS005, SPS113, MCM527, and ETH10 provide moderate (PIC = 0.25 to 0.5), and locus CSRD247, MAF70, and ILSTS11 had high value PIC > 0.5. Phylogenetic relationship was consistent with the history of its development based on Kacang goat except was for Gembrong Goat. This research information can be used for conservation strategies and breeding programs on each population of Indonesian local goat. Key Words: Local Goat, Indonesia, Microsatellites, Genetic Diversity, PIC